The Impact of Social Media Influencers and User-Generated Content on Umrah Travel Purchase Decisions in Indonesia - Rizky Ajeng Andriani; Gabrielle Meiscova Johvans Mundung; Risko Ilham Maulana (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to examine the influence of social media influencer source credibility and homophily-based user-generated content on Umrah pilgrims’ purchase decisions in the digital environment. The research adopts a quantitative approach using a survey method, with data collected from 316 respondents across Indonesia who have experience or interest in Umrah travel. Data were analyzed using Partial Least Squares-Structural Equation Modeling to evaluate both the measurement and structural models. The results indicate that influencer expertise has a positive and significant effect on purchase decisions, while trustworthiness and attractiveness do not show a significant direct influence. In addition, homophily-based user-generated content demonstrates a strong and significant effect, highlighting the importance of perceived similarity in shaping consumer confidence and reducing perceived risk. These findings suggest that Umrah pilgrims prioritize informational value, experiential relevance, and perceived similarity over visual appeal or assumed trust when making high-risk religious travel decisions. In conclusion, this study emphasizes the strategic role of expert-driven influencer credibility and authentic, homophilic user-generated content in digital marketing communication for Umrah travel services, contributing to the understanding of digital consumer behavior in high-risk and religious service contexts.